2008
DOI: 10.1007/s11060-008-9645-y
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of adjuvant chemotherapy for esthesioneuroblastoma

Abstract: This small retrospective series suggests that adjuvant therapy for patients with high grade, Stage C esthesioneuroblastoma is of benefit following complete resection. Radiation therapy alone provides an improvement in time to relapse, which may be increased further with the addition of cisplatin and etoposide based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 15 publications
2
40
1
3
Order By: Relevance
“…Chemotherapy as a neoadjuvant treatment is still under controversial debate and not recommended generally, however, one single study in a pediatric population reported promising results [8]. Other studies showed usefulness of adjuvant chemotherapy, especially in Kadish stage C high grade ONB [9]. Cisplatin-based chemotherapy, usually with etoposide, is an accepted mode of treatment in advanced, recurrent, especially high grade cases [1013], but also non-platinum schemes (irinotecan, docetaxel, doxorubicin, ifosfamide, vincristine) were described to be effective [14].…”
Section: General Informationmentioning
confidence: 99%
“…Chemotherapy as a neoadjuvant treatment is still under controversial debate and not recommended generally, however, one single study in a pediatric population reported promising results [8]. Other studies showed usefulness of adjuvant chemotherapy, especially in Kadish stage C high grade ONB [9]. Cisplatin-based chemotherapy, usually with etoposide, is an accepted mode of treatment in advanced, recurrent, especially high grade cases [1013], but also non-platinum schemes (irinotecan, docetaxel, doxorubicin, ifosfamide, vincristine) were described to be effective [14].…”
Section: General Informationmentioning
confidence: 99%
“…Mclean et al found that there is no any survival benefit when cisplatin plus etoposide was added to the surgery in patients with olfactory neuroblastoma (20). Conversely, there are retrospective studies that suggested the potential benefit of adjuvant chemotherapy in high grade and advanced stage disease (21,22). We used neoadjuvant and/or adjuvant chemotherapy in five of 14 patients, mainly combined with radiation and in advanced Kadish stage.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, si bien la incidencia de adenopatías cervicales observada en grandes series con metaanálisis se encuentra entre 15% y 20%, sólo 5% a 8% de los pacientes tiene adenopatías presentes al momento del diagnóstico. Por lo anterior, el manejo del cuello negativo es controvertido, con autores argumentando en contra y a favor del tratamiento profiláctico, especialmente en lesiones avanzadas 18 .…”
Section: Discussionunclassified